Management in industries : a pilot survey - Yesufu, T. M.; Federal Ministry of Economic Development (Lagos : National manpower board, 1968)
This study was done to provide one of the departure points for the consideration of a basic problem which will assume special importance in the context of post-war reconstruction.
Includes bibliographical footnotes.
nmn 19/04/2019
Loans
Keywords: Management; Industries; Economic development; Nigeria